The Association between Age and Sex with Rectal Cancer Metastasis Occurrence - Dhiya Nazhifah Putri; Ivan Kurniawan Bassar; Rita Halim; Moh. Rizal Syafiie; Harahap, Huntari (Jurnal Kedokteran Brawijaya, 2026)
Rectal cancer, a subtype of colorectal cancer, has shown a rising incidence; however, local epidemiological data from Jambi Province remain limited. This study aimed to determine the association between age and sex and the occurrence of metastasis among rectal cancer patients at Raden Mattaher Regional General Hospital, Jambi, from 2023 to 2025. An analytical observational study with a retrospective cross-sectional design was conducted using total sampling of 252 medical records, of which 147 subjects met the inclusion and exclusion criteria. Bivariate analysis using the Pearson Chi-square test assessed associations between variables, and multivariable Poisson regression with robust variance estimation determined the independent associations of age and sex with metastasis occurrence. Most subjects were aged 45–60 years (46.9%), male (68%), and had stage 2 disease (32.7%). Metastasis was identified in 31.3% of subjects. A significant association was found between age and metastasis (p = 0.008), with subjects aged 45–60 years showing a significantly higher prevalence ratio than the < 45-year group (PR 2.87, 95% CI 1.22–6.72). Metastasis was also significantly associated with sex (p = 0.011), with males having a 2.2-fold higher prevalence of metastasis than females (95% CI, 1.13–4.41). In the multivariable analysis, participants aged 45–60 years remained independently associated with metastasis occurrence (adjusted prevalence ratio [aPR] 2.72, 95% CI 1.17–6.30; p = 0.020). Male sex also remained independently associated with metastasis (aPR 2.09, 95% CI 1.06–4.08; p = 0.032). Conclusion: Both age and sex remained independently associated with metastasis occurrence in rectal cancer after adjustment in the multivariable analysis.